4CPS-106 Impact of oncological clinical trials in a hospital pharmacy - Lorenzo, M Gutiérrez (Eur J Hosp Pharm, 2018)
BACKGROUND: Clinical trials arise as a scientific response to the ethical need to ensure the efficacy and safety of new treatments that patients receive. Over the past few years we have seen an increase in the area of oncological clinical trials (OCT) activity. Chemotherapy preparation is considered as a complex and high-risk process. PURPOSE: To analyse the degree of activity and the economic saving of OCT. MATERIAL AND METHODS: Retrospective observational study performed in a tertiary university hospital from June 2016 to June 2017. Data was collected from PK trials(®) Active clinical trials. Ongoing OCT (non–haematological). Patients included in OCT. Dispensations. OCT dispensations. Percentage of dispensed oncological drugs (OD) provided by the promoter: number of ODs dispensed in the usual clinical practice of our centre, its cost, total savings and cost saving/patient. To calculate savings, we have used the sum of direct costs (sales prices of the laboratory published in Spain) of these drugs. RESULTS: CONCLUSION: At present, OCT prevails over those in other areas (60%) and although they imply a significant impact of economic saving on the costs of pharmaceutical treatments and the health service, activity also increases considerably (52% of total dispensations) and the care of hospital pharmacy services. In addition, preparing chemotherapies is a highly critical activity which implies an increase in the time of dispensing compared to other treatments. The role of the pharmacist is essential in order to promote the development of OCT for the benefit of patients as well as that of the public health system. No conflict of interest